(untitled) (Journal of Medical & Health Sciences Review, 2025)
Anxiety, depression, and other psychological struggles have become an urgent global concern. Spirituality has been acknowledged more and more as a major factor in psychological resilience and well-being. This study will look at the connection between God love, spirituality, and mental health by examining how faith based coping mechanisms aid in emotional stability. Informed by Attachment Theory, Pargament’s Religious Coping Theory, and Positive Psychology, the research explores how belief in a loving, comforting God may increase emotional resilience, decrease stress, and foster psychological wellbeing. This study uses a descriptive correlational research design that relies on secondary data analysis through the use of meta-analyses, clinical trials and global health reports to explore the relationship between spirituality and mental health outcomes. Findings suggest that people who feel a close tie with a benevolent higher power experience lower anxiety and depression and higher life satisfaction. In addition, the study addresses differences in cultural perspectives of God Love, exploring their implications in various traditional religious understandings. This research integrates empirical findings with existing psychological frameworks to emphasize the role of spirituality in mental health care and suggests that faith-based interventions should be incorporated into therapeutic practices.